Chacacterization of corn silage from dairy farms in the Triangulo Mineiro (Research, Society and Development, 2024)
In dairy cattle farming, corn silage is one of the main energy feeds that ensures rumen health with appropriate standards of rumination, chewing, and nutrient absorption, provided the particle size is ideal. The objective of this study was to evaluate the structural characterization of particle size in corn silage from farms located in the Triangulo Mineiro region. The mixed experimental research, conducted partly in the field and partly in the laboratory, was both qualitative (observational) and quantitative (measurements). The characterization of particle size followed the methodology of the Penn State Particle Separator. It was observed that none of the farms produced silage with the ideal corn silage particle size to ensure ruminal health and productive performance. It was found that 89.47% of the dairy farms had particles > 18mm in quantities above the standard, and 94.73% had particles < 4mm in quantities below the ideal, which implies low silage quality and food utilization below expectations. It is concluded that the farms are likely producing and performing below their potential, requiring targeted technical assistance for silage production.